Risk of perinatal mortality associated with asthma during pregnancy. Issue 2 (13th November 2008) - Breton, M-C; Beauchesne, M-F; Lemière, C; Rey, É; Forget, A; Blais, L
Abstract : Background: Thirteen studies investigating the association between asthma during pregnancy and perinatal mortality reported generally no increased risk. Most of these studies should be interpreted with caution because they were limited in terms of statistical power. A study was therefore undertaken to evaluate whether maternal asthma during pregnancy increases the risk of perinatal mortality. Methods: Through three administrative databases from Québec (Canada), a cohort of women with and without asthma who had at least one pregnancy between 1990 and 2002 was formed. Perinatal mortality was identified by diagnostic codes. The adjusted odds ratio (OR) of perinatal mortality in women with and without asthma was compared using Generalised Estimation Equation (GEE) models. The first model included all potential confounders (except small for gestational age, SGA), the second model excluded birth weight, gestational age at birth and SGA and the third model excluded birth weight, gestational age at birth but included only SGA. This analysis was also stratified for birth weight and gestational age at birth. Results: The cohort was formed of 13 100 and 28 042 single pregnancies in women with and without asthma. The crude OR of perinatal mortality was 1.35 (95% CI 1.08 to 1.67), which decreased to 0.93 (95% CI 0.75 to 1.17) after adjustment for birth weight and gestational age at birth. Women with asthma had a higher rate of low birthweight babies and preterm delivery than those without asthma. Conclusion: The increased risk of low birthweight babies and premature delivery in women with asthma may partly explain the association between maternal asthma and the increased risk of perinatal mortality.